Online Counseling Online counselling-based information services: How can it reduce students' academic stress? - Daulay, Nurussakinah; Harahap, Ade Chita Putri; Sinaga, M. Harwansyah Putra (Persona:Jurnal Psikologi Indonesia, 2023)
This study aims to reduce students' academic stress through online counselling-based information services. The experimental group consisting of one psychologist, two counsellors, and two classes of students was given online counselling-based information services help (a total of 27 students). In contrast, the control group obtained conventional information services help (a total of 25 students). The participant technique uses purposive sampling. A quasi-experimental method using a nonrandomized pretest-posttest control group design with Mann-Whitney analysis was used. The research instrument used was a stress scale, which was adapted from Fathiyah (2019) consisting of 4 aspects, namely: physical, cognitive, affective and conative, and totalling 40 items. The results showed that there was a significant difference in the academic stress effect between students who received online counselling and conventional information-based service assistance. The benefit of this research is that efforts to reduce academic stress cannot be afforded only from one counselling service, but require a variety of services, such as online counselling-based information services and conventional information services.